The Catholics and the pluralistic society, the "defective laws" and the responsibility of the legislators. - Bertone, Tarcisio (Medicina e Morale, 2001)
The article dwells on the reflection around the following question: in which measure can a Catholic citizen accept to participate in the elaboration of a law that doesn't exactly correspond to his convictions? After having illustrated the actual situation - characterised by the pluralism of the society - in which different thoughts that found upon the rights of the man coexist and that they are seen forced to negotiate for elaborating the laws and to apply them, three types of "defective" laws are illustrated: 1. the laws that allow the infringement of a fundamental human right; 2. the laws that establish a public politics that violates such a right; 3. the laws that rule some intrinsically bad actions. The author excludes, according to catholic ethics, every formal co-operation to all the three types of "defective" laws, while three attitudes: the opposition, the tolerance, the material co-operation, can be ethically justifiable. Such positions are deduced in the article with concrete examples.